Reconstructing the life of an unknown (ca. 500 years-old South American Inca) mummy--multidisciplinary study of a Peruvian Inca mummy suggests severe Chagas disease and ritual homicide. - Stephanie Panzer; Oliver Peschel; Brigitte Haas-Gebhard; Beatrice E Bachmeier; Carsten M Pusch; Andreas G Nerlich (PLoS ONE)
The paleopathological, paleoradiological, histological, molecular and forensic investigation of a female mummy (radiocarbon dated 1451-1642 AD) provides circumstantial evidence for massive skull trauma affecting a young adult female individual shortly before death along with chronic infection by Trypanosoma cruzi (Chagas disease). The mummy (initially assumed to be a German bog body) was localized by stable isotope analysis to South America at/near the Peruvian/Northern Chilean coast line. This is further supported by New World camelid fibers attached to her plaits, typical Inca-type skull deformation and the type of Wormian bone at her occiput. Despite an only small transverse wound of the supraorbital region computed tomography scans show an almost complete destruction of face and frontal skull bones with terrace-like margins, but without evidence for tissue reaction. The type of destruction indicates massive blunt force applied to the center of the face. Stable isotope analysis indicates South American origin: Nitrogen and hydrogen isotope patterns indicate an extraordinarily high marine diet along with C4-plant alimentation which fits best to the coastal area of Pacific South America. A hair strand over the last ten months of her life indicates a shift to a more "terrestric" nutrition pattern suggesting either a move from the coast or a change in her nutrition. Paleoradiology further shows extensive hypertrophy of the heart muscle and a distended large bowel/rectum. Histologically, in the rectum wall massive fibrosis alternates with residual smooth muscle. The latter contains multiple inclusions of small intracellular parasites as confirmed by immunohistochemical and molecular ancient DNA analysis to represent a chronic Trypanosoma cruzi infection. This case shows a unique paleopathological setting with massive blunt force trauma to the skull nurturing the hypothesis of a ritual homicide as previously described in South American mummies in an individual that suffered from severe chronic Chagas disease.